Minimally invasive adrenal surgery: virtue or vice?. (February 2018) - Winoker, Jared S; Ahlborn, David T; Omidele, Olamide O; Fernandez-Ranvier, Gustavo; Derweesh, Ithaar H; Mehrazin, Reza
Adrenocortical carcinoma (ACC) is a rare malignancy associated with poor prognosis despite available treatments. In patients with localized or locally advanced disease, complete resection with negative margins offers the only potential for cure. Unfortunately, most patients develop local and distant recurrence following initial resection highlighting the importance of meticulous surgical technique in the hands of an experienced surgeon. While minimally invasive surgery (MIS) has supplanted open surgery for small to medium-sized benign adrenal tumors, controversy surrounds the use of MIS for resection of ACC. We sought to provide an overview of the key oncological principles in the surgical management of ACC and to critically review the literature comparing outcomes between the open and MIS approaches.